The Implementation of Mastery Learning Model in Learn Tahfizh al-Qur’an at Madrasah Tsanawiyah in Indonesia - A. Aulia; Anna Ainun Tasbi; Sarea, Muh Syahrul (Al Bahri: Journal of Islamic Education, 2024)
The aim of this research is to increase students' interest and understanding by using educational game-based learning methods in PAI learning. This type of research is classroom action research (PTK). This research was carried out in the odd semester of the 2023/2024 academic year, starting from 3 October 2023 to 21 November 2023. This research was held at SD Inpres 5/81 Cinnong which is in Cinnong Village, Barebbo District, Bone Regency. 2nd grade students at SD Inpres 5/81 Cinnong, totaling 13 students, 10 male students and 3 female students were the subjects of this research. The object is the application of educational game-based learning methods to increase student interest and understanding. The data collection techniques used were interviews, observation and tests. Descriptive statistical analysis was used to analyze this research data. This research shows the results that when using the educational game method there is an increase in students' interest in learning from cycle I to cycle II, namely happy facial expressions in participating in learning from 7 students to 10 students. Pay attention during the learning process from 6 students to 11 students. Students do not play alone when the teacher teaches from 6 students to 11 students. trying to answer the questions given, from 4 students to 7 students. Trying to answer the questions given from 4 students to 11 students. Students' understanding also increased, in cycle 1 the students' average score was 70.77, there was an increase in cycle II with an average score of 90.